(untitled) (Research, Society and Development, 2021)
Due to its multifactorial etiology, caries disease is associated with several factors, including behavioral, environmental and socioeconomic factors, eating habits, family history of dental and past medical, previous experience of caries, as well as lack of dental services. Against the large number of factors that exist today that may be related to the onset of injury and the onset of caries disease, it is necessary to investigate the most recent scientific evidence on this subject. Therefore, the aim of this scoping review was to evidence the scientific literature on the risk factors currently related to the development of caries disease. A bibliographic research was carried out in March 2021 using the descriptors "Dental Caries"" Dental Care for Children"; "Health Education, Dental" and "Epidemiology", in electronic databases. After the selection of the articles, the data extracted from the selected articles were included in a standardized table, and the information obtained, synthesized in a table for better interpretation of the available results. Although there are several predisposing factors, most indicate that socioeconomic status, lack of dental access and eating habits are the most prevalent conditions for the onset of the disease. Due to the diversity of articles and conclusions found, comparations are difficult to be well defined. However, it is notorious the emergence of new risk factors associated with dental caries, because it is a complex disease of multifactorial etiology. Despite the variety of associated factors, it is concluded that the main predisposing factors associated with dental caries are sociodemographic and behavioral factors.